Pengaruh Persepsi Korupsi Pajak dan Kualitas Pelayanan Fiskus terhadap Kepatuhan Wajib Pajak Usaha Mikro Kecil dan Menenngah - Alpina Alpina; Ilham; Nurul Afifah (Income Journal: Accounting, Management and Economic Research, 2022)
The purpose of this study was to determine the effect of perceptions of tax corruption and the quality of tax service services on UMKM taxpayer compliance at KPP Pratama Parepare. This type of research uses quantitative research. The data used in this study are primary and secondary data using data collection techniques using questionnaires. The number of samples in this study were 100 respondents. The data analysis technique used is multiple linear regression analysis using the SPSS application. The results of this study indicate that perceptions of tax corruption and the quality of tax service services have a significant effect on UMKM taxpayer compliance at KPP Pratama Parepare. The higher the level of tax service, the higher the level of compliance. This happens because taxpayers have felt at the time of direct service which makes taxpayers feel that the services provided by tax officers affect the level of compliance. Taxpayer compliance with taxation can be influenced by the perception of corruption, this means that the perception of tax corruption plays a good role in increasing taxpayer compliance in paying taxes